(untitled) (Research, Society and Development, 2021)
Introduction: Prior planning is extremely necessary before any rehabilitation intervention, and when associated with technological advances, make clinical results safer and more stable. With the use of digital imaging exams, including radiographs, tomographies and intraoral scanning images or models, three-dimensional images of the entire bone and gingival structure can be made available, which associated with a photographic protocol, study models and diagnostic waxing, result in a decisive impact on the clinical sequence of oral rehabilitation. Objective: This paper aims to discuss a case of interdisciplinary and complex smile rehabilitation. Case Report: Patient with agenesis of dental elements 32 and 42 who was rehabilitated with implants and ceramic veneers, where from the diagnosis and interdisciplinary planning, a sequence of steps was constructed going through orthodontics, periodontics, implantology and prosthesis consecutively until the final rehabilitation. Conclusion: It is concluded that the yearning for aesthetic results is increasing and cases with severe aesthetic defects in bone and gingival architecture make it a challenge in oral rehabilitation. Reconstructive techniques combined with integrated planning and execution of specialties are the key to successful treatment of complex cases. Great advances in the field of CAD / CAM technology, allow to perform the virtual simulation of oral rehabilitation, both for the surgical stages with the installation of osseointegrated implants, as well as for prosthetic rehabilitation.